Influence of retrogression and re-aging heat treatment to stress corrosion cracking resistance on Al-Zn-Mg-Cu alloy / Deraman R., Aziz M. R. And Y. Yaakob - Deraman, R.; Aziz, M. R.; Yaakob, Y. (Research Management Institute (RMI), 2009)
The Al-Zn-Mg-Cu alloy is classified as a high strength to weight ratio material and is widely used in the aerospace structures. This alloy is susceptible to severe localized corrosion induced by heat treatment. The objective of this study is to elucidate alternative heat treatment techniques, which reduce the alloys susceptibility to Stress Corrosion Cracking (SCC). A series of different heat treatments have been performed in the Al-Zn-Mg-Cu alloy using cube shaped and C-ring specimens that had been T6- and T7-tempered and undergone Retrogression and Re-aging (RRA) heat treatments. The specimens were exposed to hardness testing, optical testing and immersion testing in a corrosive environment. The effectiveness of the heat treatments was evaluated with respect to improvements in corrosion resistance and the longevity of the Al-Zn-Mg-Cu alloy. The susceptibility of the Al-Zn-Mg-Cu alloy to SCC has been directly related to the precipitation of MgZn2 particles at the grain boundaries. Precipitation hardening of Al-Zn-Mg-Cu alloy increases the hardness of the material, but increases susceptibility to SCC failure. RRA treatment greatly improved the corrosion resistance and longevity of the alloy combined with minimal strength reduction.